\(\left(\dfrac{1}{20}-\dfrac{1}{5}\right)\cdot2^{x+1}+2^{x+2}=\dfrac{-148}{5}\)
\(\Rightarrow-\dfrac{3}{20}\cdot2^{x+1}+2^{x+1}\cdot2=-\dfrac{148}{5}\)
\(\Rightarrow2^{x+1}\cdot\left(-\dfrac{3}{20}+2\right)=\dfrac{-148}{5}\)
\(\Rightarrow2^{x+1}\cdot\dfrac{37}{20}=\dfrac{-148}{5}\)
\(\Rightarrow2^{x+1}=\dfrac{-148}{5}:\dfrac{37}{20}\)
\(\Rightarrow2^{x+1}=-16\)
Xem lại bài
\(\left(\dfrac{1}{20}-\dfrac{1}{5}\right)\cdot2^{x+1}+2^{x+2}=-\dfrac{148}{5}\)
\(\Leftrightarrow-\dfrac{3}{20}\cdot2^{x+1}+2^{x+1}\cdot2=\dfrac{-148}{5}\)
\(\Leftrightarrow2^{x+1}\left(-\dfrac{3}{20}+2\right)=\dfrac{-148}{5}\)
\(\Leftrightarrow2^{x+1}\cdot\dfrac{37}{20}=\dfrac{-148}{5}\)
\(\Leftrightarrow2^{x+1}=\dfrac{-148}{5}:\dfrac{37}{20}\)
\(\Leftrightarrow2^{x+1}=-16\)
\(\Leftrightarrow2^{x+1}=-2^4\)(vô lí)
Xem lại đề bài!